Analisis Kepuasan Pengguna Terhadap Penggunaan Website Berita Online Dalam Meningkatkan Pelayanan Publik Pada Kantor Camat Medan Polonia Menggunakan Metode End User Computing Statisfaction (EUCS) - Windiyani Barus; Mesran (ADA Journal of Information System Research, 2023)
The Online News Website is a site that is used as a source of information on the Medan Polonia District Head Office Website. Previously, the system that was being implemented had many shortcomings, therefore a website was created in the hope that it could help the Medan Polonia Subdistrict Office employees in facilitating the dissemination of information to the public. This website was created using a database programming language, and has several features, namely display of search data filter menus, news categories, user comments, statistical data, contact and complaint services and development programs, as well as links to other resources.